Delinquent Behavior and Gender Differences: a Verification of Situational Action Theory (According to the Results of an International Study on Delinquency, Attitudes and Victimization (ISRD-3)) - JUSTICKAJA, SVETLANA; GIEDRYTĖ-MAČIULIENĖ, RENATA (Kriminologijos studijos, 2017)
Over the years, many studies were done in order to analyze gender differences in delinquent behavior. Most often delinquent and criminal behavior is understood as a male problem. Therefore, two fundamental questions are raised in the context of studies on gender differences in delinquency and crime: why are women/girls less involved in offending (and, at the same time, why do men/boys are more likely to commit offences) and whether their delinquent and criminal behavior could be explained by the same reasons. This article investigates to what extent a recent perspective in criminology, the Situational Action Theory, is valid for both boys and girls and to what extent do elements from this theory explain gender differences in delinquency in Lithuania. The verification of the Situational Action Theory was based on the results of the Third International Self-Report Delinquency Study (ISRD-3).ISRD-3 in Lithuania was carried out in five cities (Vilnius, Šiauliai, Kretinga, Plungė and Telšiai). 2 824 pupils from 7th, 8th and 9th grades were surveyed. They represent the following age groups: 12-13, 13-14 and 14-15. 128 questionnaires were found not suitable for analysis. 49 percent (1 320) of all respondents were girls and 51 percent were boys (1 376). First, correlations between the elements of the Situational Action Theory – morality, self-control, unsupervised peer activity, rule-breaking peers, bonds with parents, parental monitoring, a bond with school – and delinquent behavior were counted. Second, a regression analysis was conducted.The results of the investigation revealed the fact that not all the assumptions of the Situational Action Theory could be confirmed. What is more, gender differences in delinquent behavior could be explained by different elements of the Situational Action Theory. Two elements (rule-breaking peers and morality) are consistent with the Situational Action Theory and could explain the delinquent behavior of both boys and girls. Self-control is more relevant in predicting the delinquent behavior of boys, whereas bonds with parents and parental monitoring are important predictors of delinquency among girls. Unsupervised peer activity and a bond with school could not be related to the delinquent behavior of both boys and girls. Therefore, only separate elements mentioned in the Situational Action Theory were related to delinquency and to the gender gap in delinquency.
Keywords: delinquent behavior; gender; Situational Action Theory